Queering the Amateur Analog Video Archive: The Case of Bologna’s Countercultural Life in the 80s and the 90s (Cinéma & Cie. Film and Media Studies Journal, 2016)
Drawing on an interdisciplinary approach, this article aims to outline some theoretical issues concerning the archival structure of videos developed during the Eighties and the Nineties in Bologna’s alternative scene. More specifically, we will focus on two archives, Cassero CDOC Centre’s video archive and Home Movies — the Italian National Amateur Film Archive, which host two different video repositories that stemmed from a common background: Bologna’s countercultural environment, in which we can find the “1990 Student Movement” (the so-called Pantera) and the gay and lesbian scene that belonged to Arcigay and Il Cassero. These materials shared not only some production/fruition modalities, but, very often, the same people took part in them: we can see members of the gay community who were, in the meantime, students who participated in the university occupations. Therefore, the main questions we have to answer are: which kind of archival framework is the most appropriate for such materials? Are the current archival practices correct in order to abide by the original context and motivations that fostered their production? Our reply refers to the notion of transarchive.